Advancing the chemistry of monovalent phosphorus - Duffy, Matthew Philip (2012)
This thesis documents our attempts to advance the chemistry of monovalent phosphorus. To advance the chemistry of monovalent phosphorus one must incorporate new substituents on phosphorus, and/or find new substrates with which to trap the terminal phosphinidene complexes with. This thesis consists of seven chapters. Chapter one is an introduction to phosphinidene chemistry. It describes the transition from phosphinidene chemistry to terminal phosphinidene chemistry. Chapter one goes on to describe the different methods to generate terminal phosphinidene complexes, extensively lists reactions done with them, provides a brief overview of the types of reactions that they can do, and ends by describing ways of removing the transition metal from phosphorus of the newly generated organophosphorus species. Chapter two describes the generation and trapping of a chlorophosphinidene complex, which was achieved starting from an improved synthesis of 1-chloro-3,4-dimethylphosphole tungsten complex. Chapter three is a direct application of the chlorophosphinidene complex, which provides a straightforward synthesis to 2-phosphafurans, one of the least well-known members of the heterophosphole family. Also some preliminary results concerning its chemistry are provided. Chapter four describes the generation of a hydroxyphosphinidene complex and our attempts to use it as a source for making new phosphinous acids. With our new synthetic routes to the chlorophosphole and hydroxyphosphole, chapter five describes how we use these building blocks to generate P-X-P-linked biphosphole complexes (X = O, S). We discovered that a minor change in the structure leads to a complete shift from the [4+2] to the [2+2] dimerization. Chapter six describes the reaction of terminal phosphinidene complexes with dihydrogen, where the end product is similar to the reaction of dihydrogen and carbenes, although the reaction conditions are harsher and the mechanism of the reaction is quite different. Chapter seven describes the reaction of terminal phosphinidene complexes with silanes, which lead to primary phosphine complexes.